An examination of Some Commonly Utilized Techniques for Perception of Secret Writing (Indian Journal of Forensic Medicine & Toxicology, 2020)
Secret writing is the art of covered or hidden writing. The art of secret writing is meant to create a messageunreadable by a third party however doesn’t hide the existence of the secret communication. This paper ismeant as a technical introduction to secret writing for those unacquainted with the field. Invisible inks aregenerally used for secret writing. These are fluids used to write hidden messages that do not appear unlessexposed by a revealing process. Invisible inks can be classified into three main categories: those that arerevealed by heat, those revealed by chemical reactions and those that are visible under ultraviolet light.Some common household invisible inks are diluted fruit juices, vinegar and laundry detergent, all which canbe applied by a paintbrush, special invisible ink pen or even a toothpick, Historically, used in times of warby governments and insurgents alike. The chemical processes of invisible inks are well known, so a varietyof detection methods exist. The simplest invisible ink experiment consists of dipping a brush in vegetablejuice, biological fluids and different chemicals and writing on a piece of blank varieties of paper. When the“ink” dries, it will be invisible to the naked eye, but if the paper is held up to a moderate heat source such asa light bulb, a radiator or an iron using UV lamp to deciphering invisible writing. Many other mild chemicalsalso used for restoration of secret writing.